2004
DOI: 10.1111/j.1523-1755.2004.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition in patients with acute renal failure

Abstract: Enteral nutrition is a safe and effective nutritional technique to deliver artificial nutrition in ARF patients. Parenteral amino acid supplementation may be required, especially in patients with ARF needing renal replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 31 publications
1
42
0
2
Order By: Relevance
“…This finding is similar to the results published in critically ill adult patients with acute renal failure (Fiaccadori et al, 2004). The higher incidence of complications in patients with acute renal failure could be due the gastrointestinal motility disorders associated with the uremia (Van Vlem et al, 2000) and/or the greater clinical severity of patients with acute renal failure indicated by the higher incidence of shock, the need for high drugs of vasoactive doses and multiorgan failure (Fernández et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to the results published in critically ill adult patients with acute renal failure (Fiaccadori et al, 2004). The higher incidence of complications in patients with acute renal failure could be due the gastrointestinal motility disorders associated with the uremia (Van Vlem et al, 2000) and/or the greater clinical severity of patients with acute renal failure indicated by the higher incidence of shock, the need for high drugs of vasoactive doses and multiorgan failure (Fernández et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…ABH'da enteral beslenmeye dair veriler kısıtlıdır. Nazogastrik tüp yoluyla verilen beslenme desteğinin güvenilirlik ve etkinliği 182 ABH'lı hastada değerlendirilmiş ve ABH ile GI, mekanik veya metabolik komplikasyonlarda artış arasında bir ilişki saptanmamıştır (41). Yüksek gastrik rezidüel volüm böbrek fonksiyonu normal hastalarla karşılaştırıldığında ABH'lı hastalarda daha sık gözlenmiştir.…”
Section: Eser Elementlerunclassified
“…Bu formüllerin dezavantajı protein konsantrasyonunun daha düşük ve bazı elektrolit düzeylerinin (potasyum, fosfat) daha yüksek olmasıdır. Kronik böbrek yetmezliği olan hastalar için düzenlenmiş formüller ABH'lı hastalarda da kullanılabilir (41). Bu formüller, standart formüllerin birçoğu ile karşılaştı-rıldığında, daha yüksek kalori, daha düşük elektrolit içeriği ve bazılarında daha yüksek protein oranı ile karakterizedir.…”
Section: Eser Elementlerunclassified
“…However, when patients are unable to consume adequate nutrition, tube feedings may be implemented. In an observational study by Fiaccadori et al [45], EN-related complications and the adequacy of nutrient administration during 2525 days of EN were compared in 247 consecutive patients fed exclusively by the enteral route (65 normal renal function, 68 AKI not requiring RRT, 114 AKI requiring RRT). The investigators found no difference in gastrointestinal or mechanical complications between AKI patients and patients with normal renal function, except for high gastric residual volumes (not defined), which occurred in 3.1% of patients with normal renal function, 7.3% of patients with AKI not requiring RRT, 13.2% of patients with AKI requiring RRT (P = 0.02 for trend), and for nasogastric tube obstruction: 0.0%, 5.9%, 14%, respectively (P < 0.001).…”
mentioning
confidence: 99%
“…EN was safe and effective in patients with AKI. In patients experiencing intolerance to gastric feedings, clinicians are encouraged to try small-bowel feedings [45]. !…”
mentioning
confidence: 99%